Training Strategies for Practical Ability of College Students Majoring in Computer-Aided Design - Liu, Xingde (International Journal of Emerging Technologies in Learning (iJET), 2020)
Currently, the college students majoring in computer-aided design (CAD), a discipline under the department of mechanical engineering, generally have a poor ability to solve engineering problems. Therefore, this paper attempts to design effective training strategies to improve the practical ability of the CAD majors. Firstly, the authors highlighted the promoting effect of the CAD on the practical ability of college students, and summed up the prob-lems of college students in the engineering application of the CAD. On this basis, several strategies were put forward to improve the practical ability of the CAD majors from three aspects: CAD curriculum planning, CAD practi-cal training and CAD platform construction. To verify the effectiveness of the strategies, an index system was established based on information entro-py, and organized into an evaluation model through expert scoring. The strategies and evaluation model provide strong supports to the training of practical ability for the CAD majors.